1998
DOI: 10.1038/sj.bjp.0701768
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of vascular function in rat mesenteric resistance arteries following cold storage, studied by small vessel myography

Abstract: 1 The use of isolated blood vessels to investigate the physiological and pharmacological control of the vasculature is limited by the requirement to use freshly isolated vessels. Hence, the aim of this study was to determine whether vascular smooth muscle and endothelial cell function could be preserved in resistance arteries by storing them in physiological salt solution (PSS) at 48C. 2 Third order mesenteric resistance arteries (mean internal diameter 237+6 mm) were dissected from the mesenteric bed of male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…It was also anticipated that preservation in UW solution would not alter the contractile function of donor hepatic arteries. We have shown that the function of rat mesenteric arteries is unaltered after 3 days in a physiological salt solution [19] and UW solution has been shown to preserve the contractile function of porcine [20] and human [18] hepatic arteries. Our results confirmed that the comparison of responses in donor (stored in UW solution) and recipient (removed immediately from the explanted liver) hepatic arteries was valid in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It was also anticipated that preservation in UW solution would not alter the contractile function of donor hepatic arteries. We have shown that the function of rat mesenteric arteries is unaltered after 3 days in a physiological salt solution [19] and UW solution has been shown to preserve the contractile function of porcine [20] and human [18] hepatic arteries. Our results confirmed that the comparison of responses in donor (stored in UW solution) and recipient (removed immediately from the explanted liver) hepatic arteries was valid in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Cord segments were cut at least 10 cm from the infants and were placed into a modified Krebs solution (Na + 151 m M , K ) and stored at 4 ° C for less than 48 h until the experiments. Up to 3 days of storage of blood vessels under these conditions did not affect vessel function [15] .…”
Section: Vessel Dissectionmentioning
confidence: 99%
“…The study was approved by the local ethics committee. Within the first minutes of birth, cord segments were cut at least 10 cm from the infants, because the distal part of the human umbilical vein is thought to be definitely devoid of nerves (4,21 (14). At the end of our experiments, KCl was added to a final concentration of 0.05 M to test the viability of the preparations.…”
Section: Vessel Dissectionmentioning
confidence: 99%